“Stay the fuck at home!”: Feminism, family and the private home in a time of coronavirus - Kay, Jilly Boyce (Feminist Media Studies, 2020)
This short essay considers how, in conditions of widespread lockdown during the coronavirus pandemic, domestic space has become hyper-visible. It argues that, in the mediated aesthetics of the crisis, we have seen a resurgence of mystificatory images of the heteronormative private household through celebrity culture. It considers how the injunction to ‘stay the fuck at home’ may work to conceal pervasive forms of gendered violence within domestic space, as well as re-affirming the private, capitalist home as a place of safety and stability. Drawing on the work of family abolitionist feminism, the essay argues that we might turn the hyper-visibility of the private heteronormative home against itself, by exposing its inbuilt dangers, inequalities, and cruelties - and by imagining how much better home could be.
Keywords: 2000 à aujourd'hui; 2010-2019; 2020-2029; approches et analyses; communication; covid-19; discipline; espace domestique; hétérosexisme; inégalités; périodes historiques; représentations médiatiques; ressource en ligne; systèmes d'oppressions; thématiques; violences